Thursday
March 23, 2017

Post a New Question

Posted by on Monday, April 1, 2013 at 5:09pm.

I need help solving this equation.

3√z+1=-3

How do I do this problem? Thanks for your help.

  • college algebra - , Monday, April 1, 2013 at 5:34pm

    3√z+1 = -3
    3√z = -4
    Now, √z is interpreted to be positive
    √4 = 2, not ±2
    so, there is no solution to the equation
    3√z = -4
    since √z is positive

    However, we can go on to say that

    3√z = -4
    9z = 16
    z = 16/9

    But, this is really a spurious solution, since

    3√(16/9)+1 = 3(4/3)+1 = 4+1 = 5
    We cannot use -4/3 as √(16/9) unless specifically indicated.

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question